El impacto del boom latinoamericano en los escritores serbios - Kovačević Petrović, Bojana (Acta Hispanica, 2016)
In this work we want to show the strong links between Spanish-American and Serbian writers, through the books translated from Spanish and works written in Serbian. Assuming that each writer is above all a good reader, and considering the importance of translation for literature in general, we have investigated the influence of Borges, Cortázar, Fuentes, García Márquez and Vargas Llosa on Serbian writers since the 1950s until today. Through authentic testimonies - interviews made for this research - and the reviews and analysis of books and particular texts influenced by the authors of the boom, we will present a creative variety and authentic literary creation of a small country with many translations and dedicated writers, and show that the great impact of Spanish-American literature in Serbia began half a century ago and never ceased.